ADOPTION OF THE RECOMMENDED POTATO PRODUCTION TECHNOLOGY BY THE POTATO GROWERS OF THE JAMMU DIVISION - Peer, Quadri JA; Kher, S K; Peshin, Rajinder; Ahmad, Nafees; Kaur, Jasvinder; Bhat, F N (Potato Journal, 2013)
Â